KAJIAN WACANA KRITIS MODEL SARA MILLS PADA TEKS BERITA ONLINE - Irtantia, Evitamara; Mulawarman, Widyatmike Gede; Yahya, Masrur (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This research is motivated by news that is increasingly free in expression in online media. Society is presented with taboo news such as sexual harassment. Foksu research is a critical discourse analysis on sexual harassment of women online media edisis January- February 2022. The importance of conducting this research is that researchers want to reveal the purpose of news writing by looking at how women are positioned in the news. the purpose of this study is to describe a critical discourse analysis on sexual harassment of women in the January-February 2022 edition of online media. This research is a qualitative descriptive research using a critical discourse analysis approach. The data in this study is in the form of langsu quotes in the form of words, phrases, clauses, sentences, or paragraphs that indicate the position of the subject, object and reader. The source of the data is a news discourse in several online media outlets containing about sexual harassment of women in the January- February 2022 edition. The data collection technique used in this study was to use the listen and record technique. Helpful data collection instruments that assist the research in conducting this research are news texts, papers, highlighters, laptobs, pens and data cards. The severity of the data used is the persistence of observations and the triamgulation of peers. The analysis technique uses Sara Milles data, namely the reduction stage, data presentation, and drawing conclusions. The results of the study were 15 data selection data in the form of news texts from online media, which included 5 data detiknews.com, Liputan6 as much as 1 news, detiknews as many as 6 news, Kompas com as many as 1 news, Tribun, East Kalimantan as many as 2 news, cakapkalah.com as many as 1 news containing sexual harassment of women in the January-February 2022 edition of online media. The news dominates the position of men and women is marginalized. The reader's position to follow the flow of the newswriter.